Correlates of retention in HIV care after release from jail: results from a multi-site study. - Althoff, Amy L; Zelenev, Alexei; Meyer, Jaimie P; Fu, Jeannia; Brown, Shan-Estelle; Vagenas, Panagiotis; Avery, Ann K; Cruzado-Quiñones, Jacqueline; Spaulding, Anne C; Altice, Frederick L (AIDS and behavior, 2013)
Retention in care is key to effective HIV treatment, but half of PLWHA in the US are continuously engaged in care. Incarcerated individuals are an especially challenging population to retain, and empiric data specific to jail detainees is lacking. We prospectively evaluated correlates of retention in care for 867 HIV-infected jail detainees enrolled in a 10-site demonstration project. Sustained retention in care was defined as having a clinic visit during each quarter in the 6 month post-release period. The following were independently associated with retention: being male (AOR = 2.10, p ≤ 0.01), heroin use (AOR 1.49, p = 0.04), having an HIV provider (AOR 1.67, p = 0.02), and receipt of services: discharge planning (AOR 1.50, p = 0.02) and disease management session (AOR 2.25, p ≤ 0.01) during incarceration; needs assessment (AOR 1.59, p = 0.02), HIV education (AOR 2.03, p ≤ 0.01), and transportation assistance (AOR 1.54, p = 0.02) after release. Provision of education and case management services improve retention in HIV care after release from jail.
Keywords: Adult; Case Management; Continuity of Patient Care; Female; Follow-Up Studies; Health Services; Health Services Accessibility; HIV Infections; Humans; Male; Middle Aged; Patient Compliance; Patient Discharge; Prisoners; Prisons; Prospective Studies; Secondary Prevention; Social Support; Social Work; Socioeconomic Factors; Young Adult